miR-122 removal in the liver activates imprinted microRNAs and enables more effective microRNA-mediated gene repression - Paul N. Valdmanis (Nature Portfolio, 2018)
miR-122 is a highly expressed microRNA in the liver. Here the authors analyse the mouse liver microRNA landscape following depletion of miR-122 and the impact that this has on its target mRNAs.